A “REVOLTA” DE JEÚ E A ESTELA DE DÃ: Um Estudo Em 2 Reis 10,28-36 - SOUZA, BRUNO CAVALCANTE DE (2016)
The research aims to work the event of Jehu's revolt, together with the stele of Dan, taking as a starting point for such exegesis of the perícope of 2 Kings 10 to 28.36. The story Deuteronomist presents the act of Jehu's revolt as an important achievement too, the cult of the restoration to the Lord in Israel, from a context where the worship of other deities in Israel North, was in full swing. However, from the joint analysis of the stele of Dan, whose probable author King Hazael of Damascus, we are challenged to read this story between the lines not covered by the text, pointing to an active participation of Hazael on outcomes related to revolt of Jehu as being directly responsible that gave the rise of Jehu king in Israel, thus clarifying this important period in the Biblical story. For this analysis, it will be observed three distinct topics directly related to the proposed theme: (1) The Revolt of Jehu and the Deuteronomist Writing, from the exegetical study of the perícope of 2 Kings 10.28 to 36, which are described timely information about the period in which Jehu reigned in Israel; (2) Jehu and the Stele of Dan, from the presentation and analysis of the contents of the stele of Dan, comes directly from the war unfolding in Ramoth-Gilead, where takes place the starting point of the revolt of Jehu; and finally (3) The Empire of Syria, where from the ongoing analysis of the contents of the stele of Dan demonstrate the significance of this kingdom, and notes directly related to the reign of Hazael very important character in the Revolt of Jehu event